Self-assessment of adults with acquired hearing loss in the context of self-esteem and psychosocial functioning - Jasmina Karić; Milena Kordić; Gorica Vuksanović; Jana Mitrić (Биомедицинска истраживања, 2023)
Introduction: The consequences of acquired hearing loss in adults condition their psychosocial functioning and imply changes in the quality of life related to disorders in social and emotional functioning. Hearing loss is considered a risk factor for reduced psychosocial functioning and self-esteem. Psychosocial well-being and preserved self-esteem imply having a positive self-image and realizing that a person is an important part of the social community in which he/she lives. The paper deals with self-esteem and psychosocial functioning of adults with acquired hearing loss. The aim of this research is to determine the level of self-esteem and the degree of expression of consequences in psychosocial functioning, that is, the connection between the level of self-esteem and the degree of expression of consequences in psychosocial functioning in adults with acquired hearing loss. Methods: The research was conducted on a sample of 60 adult subjects with acquired hearing loss and 60 subjects with normal hearing. The average age of the respondents with hearing loss was 54.1 (SD = 10.84), and the sample consisted mostly of male respondents (56.7%) with moderate hearing loss (25.4%). The Rosenberg Self-Esteem Scale and the questionnaire for the subjective assessment of the hearing condition - the HHIA questionnaire (Hearing Handicap Inventory for Adults) were used as instruments. Results: The results showed that the respondents expressed moderate or average self-esteem and that there was a connection between self-esteem and psychosocial functioning in adults with acquired hearing loss. Conclusion: Future research could be directed more towards examining self-esteem in more detail in more specific domains of psychosocial functioning of adults with acquired hearing loss.
Keywords: hearing loss; adults; self-esteem; psychosocial functioning